Effect of Music on Cardiovascular Reactivity and Pain Tolerance During Cold Pressor Test - Jha, Rakesh Kumar; Myneedu, Vithal Prasad; Shah, Gaurab Jung; Shah, Rajesh (Medical Journal of Eastern Nepal, 2025)
Background Music has been proposed as a low-cost non-pharmacological intervention for stress and pain reduction. This study evaluated the effects of music on blood pressure, pulse, and pain tolerance during the cold pressor test (CPT) in healthy adults. Methods A within-subject crossover study was conducted on 80 healthy medical students (20–30 years). Four randomized conditions were tested: rest, music, CPT, and CPT+music. Blood pressure, pulse, SpO₂, and pain tolerance were measured. Paired t-tests compared conditions. Results Music significantly reduced resting systolic BP and pulse, attenuated CPT-induced increases in BP and pulse, and markedly increased pain tolerance. SpO₂ remained stable. Effect sizes were large. Conclusion Music reduces cardiovascular reactivity and enhances pain tolerance during CPT. It may serve as a safe, low-cost adjunct in stress and pain management.